Mentorship within Doctoral Research Assistantships: A Canadian Case Study - Niemczyk, Ewelina Kinga (Alberta Journal of Educational Research, 2019)
This article explores research assistantship (RAship) experiences of doctoral students in one program in a Faculty of Education at a Canadian university in the province of Ontario during a specific period of time. Doctoral students’ development as researchers is a key objective in higher education institutions nationwide. RAships provide opportunities in which doctoral students can be mentored and nurtured as future researchers. However, few scholars have investigated mentoring relationships within doctoral RAships, which are rooted in research assistants’ (RAs’) lived experiences. Data for this case study were drawn from personal interviews with six doctoral students and complemented by the voices of five research supervisors and two administrators. Findings show that although RAships offer the potential for mentorship, not all RAships involve mentoring relationships. Some of the uncovered relationships between RAs and their supervisors were positive while some seemed exploitative. Results indicate that, to various degrees, research supervisors control the experiences to which RAs are exposed. Given the results of this research, more comprehensive studies are needed to identify how research supervisors might engage more effectively in inherently unequal collaborations with RAs. Keywords: research assistantships, mentorship, doctoral students, power dynamics, case study Cet article porte sur les expériences de doctorants travaillant comme assistants à la recherche dans un programme de la faculté d’éducation d’une université canadienne dans la province de l’Ontario pendant une période déterminée. Partout au Canada, les établissements d’études supérieures ont comme objectif majeur de développer leurs doctorants en chercheurs. Les postes d’assistants à la recherche offrent à ces étudiants un encadrement et un mentorat qui les soutiennent alors qu’ils sont en voie de devenir chercheurs. Toutefois, peu de recherches se sont penchées sur les expériences des doctorants dans la relation de mentorat découlant des postes d’assistants à la recherche. Les données de cette étude de cas proviennent d’entrevues personnelles auprès de six doctorants, et de contributions de la part de cinq directeurs de recherche et deux administrateurs. Les résultats indiquent que si les postes d’assistants à la recherche offrent la possibilité d’une relation de mentorat, cette relation n’est pas présente dans tous les postes. Certaines des relations entre les assistants à la recherche et les doctorants se sont avérées positives alors que d’autres semblaient abusives. Les résultats indiquent que les directeurs de recherche contrôlent, à divers degrés, les expériences auxquelles sont exposées les assistants à la recherche. Compte tenu de ces résultats, il serait important d’entreprendre des études plus approfondies pour identifier les façons dont les superviseurs pourraient mieux s’engager dans des collaborations, qui sont inégales à la base, avec les assistants à la recherche. Mots clés : postes d’assistants à la recherche; mentorat; doctorants; dynamique du pouvoir; étude de cas